SUMBER STRESS AKULTURASI DAN COPING STYLE PROFESIONAL INDONESIA DI SINGAPURA - Inge Kurniawati Anwar (MANASA, 2012)
Cross-cultural living is not a new thing. In fact, living and working in an other country is already part of the globalization era. The intercultural adjustment between contries called acculturative process. The acculturative process is not easy, frequently caused conflicts and acculturative stress. My research objective is to map specific acculturative stressors experienced by Indonesian expatriate worker at Singapore, their coping style, and also to explore the intervention needed to reduce or overcome the stressors. The research has been done by using close-ended working and open-ended questionnaires, answered 63 Indonesian expatriate who has been working and living at Singapore for at least 6 months. Based on the analysis result, the aculturative stressor that has been experienced by the respondents fall into five dimension: Occupational and Financial Mobility, Cultural Differences-Achievement, Cultural Difference-Speed, Cultural Difference-Competiveness, and Biological (food) stressor. Stress coping style that has been used effectively by most respondent is active problem coping. Before going to Singapore, cultural orientation program that provoke cultural awareness is needed, in order to avoid or reduce negative effect of acculturative stress and to adapt successfully.